2018
DOI: 10.1080/15548627.2018.1528812
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic expression of a ratiometric autophagy probe specifically in neurons enables the interrogation of brain autophagy in vivo

Abstract: Autophagy-lysosome pathway (ALP) disruption is considered pathogenic in multiple neurodegenerative diseases; however, current methods are inadequate to investigate macroautophagy/autophagy flux in brain in vivo and its therapeutic modulation. Here, we describe a novel autophagy reporter mouse (TRGL6) stably expressing a dual-fluorescence-tagged LC3 (tfLC3, mRFP-eGFP-LC3) by transgenesis selectively in neurons. The tfLC3 probe distributes widely in the central nervous system, including spinal cord. Expression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 52 publications
3
80
0
Order By: Relevance
“…Lysosomal pH was significantly higher in DS fibroblasts than in 2N cells (pH ϭ 5.03 Ϯ 0.08 vs 4.66 Ϯ 0.06, t (92) ϭ 8.414, p Ͻ 0.0001; unpaired t test). We confirmed the lysosomal acidification deficit in DS fibroblasts by expressing in the cell lines a tandem fluorescent-tagged LC3 (mRFP-eGFP-LC3) probe, which has been used to monitor autophagic flux (Kimura et al, 2007;Lee et al, 2010Lee et al, , 2019Zhou et al, 2012). We combined transfection of this construct with the uptake and lysosomal delivery of dextran-AlexaFluor-647 to fluorescently mark lysosomes.…”
Section: Lysosomal Acidification Deficiency In Ds Fibroblastsmentioning
confidence: 76%
See 1 more Smart Citation
“…Lysosomal pH was significantly higher in DS fibroblasts than in 2N cells (pH ϭ 5.03 Ϯ 0.08 vs 4.66 Ϯ 0.06, t (92) ϭ 8.414, p Ͻ 0.0001; unpaired t test). We confirmed the lysosomal acidification deficit in DS fibroblasts by expressing in the cell lines a tandem fluorescent-tagged LC3 (mRFP-eGFP-LC3) probe, which has been used to monitor autophagic flux (Kimura et al, 2007;Lee et al, 2010Lee et al, , 2019Zhou et al, 2012). We combined transfection of this construct with the uptake and lysosomal delivery of dextran-AlexaFluor-647 to fluorescently mark lysosomes.…”
Section: Lysosomal Acidification Deficiency In Ds Fibroblastsmentioning
confidence: 76%
“…We combined transfection of this construct with the uptake and lysosomal delivery of dextran-AlexaFluor-647 to fluorescently mark lysosomes. Fusion of APs with normally functioning lysosomes rapidly lowers the pH within resulting autolysosomes (ALs) (Lee et al, 2019). In this triple-fluorescence labeling paradigm ( Fig.…”
Section: Lysosomal Acidification Deficiency In Ds Fibroblastsmentioning
confidence: 93%
“…We and others have demonstrated that Parkin‐mediated mitophagy primarily occurs in the soma of neurons, where degradative lysosomes are highly enriched (Cai et al , , 2012b; Devireddy et al , ; Xie et al , ; Ye et al , ; Maday & Holzbaur, ; Sung et al , ; Lin et al , ; Tammineni et al , 2017a; Cheng et al , ; Lee et al , ). We next examined whether Rheb is important for Parkin‐mediated mitophagy.…”
Section: Resultsmentioning
confidence: 92%
“…It is well established that proteolytically active lysosomes are highly enriched in the soma of neurons (Cai et al , , 2012b; Gowrishankar et al , ; Xie et al , ; Maday & Holzbaur, ; Tammineni et al , 2017a; Cheng et al , ; Yap et al , ; Lee et al , ). We and others have shown that impaired lysosomal proteolysis results in lysosomal accumulation of undigested substrates, including autophagy cargoes, in the neuronal soma (Cai et al , , 2012b; Xie et al , ; Maday & Holzbaur, ; Tammineni et al , 2017a; Cheng et al , ; Lee et al , ). Consistent with somatic localization of mature lysosomes in neurons, previous studies reported that acidic mitochondria can be detected in the soma, but not in the axons of neurons (Bingol et al , ; Puri et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…LC3, p62 and LAMP1 were chosen as the selective markers for the above three steps, respectively. 3-MA, one of the autophagy inhibitors, was used to inhibit autophagosome formation by interrupting PI3K/AKT/mTOR signaling, while CQ, one of the lysosome inhibitors, was utilized to inhibit autophagic flux and lysosomal function by blocking lysosomal acidification [33]. To determine which steps are involved in the effects of URB on CCHinduced NLRP3 inflammasome activation, we examined the expressions of NLRP3, LC3, p62 and LAMP1 and their colocalization in the hippocampus.…”
Section: Urb Alleviates Cch-induced Nlrp3 Inflammasome Activation By mentioning
confidence: 99%